TRAUMA AND SPACE: THE SYMBOLIC ROLE OF SETTING IN CONTEMPORARY WAR NARRATIVES - Dusanova Muqaddas Xudayshukur qizi (International Journal of Literature and Language Studies, 2026)
This article examines the relationship between traumatic experience and spatial representation in contemporary war narratives, arguing that the literary settings of such texts function not merely as physical backgrounds but as symbolic repositories of collective and individual trauma. Drawing on Bakhtin's concept of the chronotope, Gaston Bachelard's poetics of space, and established frameworks in trauma studies, the article investigates how destroyed, contested, and remembered landscapes are constructed through metaphorical and figurative language to encode the psychological, moral, and cultural dimensions of wartime suffering. Through close analysis of Khaled Hosseini's The Kite Runner, the article demonstrates that spatial settings in contemporary war narratives undergo a progressive symbolic transformation across the narrative arc, shifting from sites of belonging and innocence to sites of rupture, guilt, and partial redemption. The findings suggest that the symbolic spatialization of trauma constitutes a defining feature of the contemporary war narrative as a literary genre, and that stylistic analysis offers essential tools for uncovering the mechanisms through which this spatialization is achieved.